ANALISIS EFEKTIVITAS MESIN PARKIR MOTOR KAMPUS UNTAR 1 DENGAN METODE LEAN SIX SIGMA (DMAIC) - Sherly; Dina Amalia Julia Kristaliantri; Della Putri Setianingrum; Andrew Johnson Wijaya; Lithrone Laricha Salomon (Jurnal Ilmiah Teknik Industri, 2025)
This study aims to analyze the effectiveness of the motorcycle parking service at Untar Campus 1 using the Lean Six Sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) approach. The main problems identified included the high frequency of tap-out errors, such as unreadable cards, slow reader performance, and delayed staff responses, which caused long queues and reduced user satisfaction. The research was conducted through field observations, questionnaires distributed to 60 respondents, and data collection using Time Observation Sheets (TOS) and Check Sheets. The results showed that the “unreadable card” error was the dominant issue, accounting for 66.67% of total incidents. The average staff response time was 137.6 seconds, while the average machine repair time was 58.5 seconds. Pareto and 5 Why’s analysis revealed that the main root cause was the lack of preventive maintenance on reader sensors and the absence of consistent maintenance SOPs. Improvement proposals were implemented through the application of Poka-Yoke, 5S, and Kaizen Event to improve process efficiency, reduce human error, and accelerate error handling. The study concludes that the implementation of Lean Six Sigma was able to improve parking service effectiveness and service quality for users.